Accounting conservatism: A review of the literature. Issue 1 (February 2015) - Ruch, George W.; Taylor, Gary
Abstract: We review and analyze the accounting literature that examines the effects of accounting conservatism on financial statements and financial statement users. We begin by analyzing how conservatism affects the reported numbers on the financial statements. These studies primarily evaluate how conservatism affects earnings quality, including earnings persistence and the presence of earnings management. Next, we assess the effect of accounting conservatism on the users of the financial statements. We identify three primary users of the financial statements: (1) equity market users (2) debt market users and (3) corporate governance users. Within each of these categories, we analyze the findings of prior research and explore unanswered research questions. By analyzing the effects of accounting conservatism from a diverse range of research topics, we inform the discussion on the costs and benefits of accounting conservatism.